STUDY AND ANALYSIS OF THE MICROBIOLOGICAL COMPOSITION OF OPEN RESERVOIRS - Jumaeva Sh.B (Galaxy International Interdisciplinary Research Journal, 2023)
When assessing water quality, conducting hydrobiological studies along with conducting sanitary and microbiological studies in open reservoirs of the Bukhara region is considered necessary. The survival rate of pathogenic and opportunistic microorganisms in the water of reservoirs increases due to an increase in the diversity of microorganisms, including benthos, phytoplankton and zooplankton.